Pancosmorio (world limit) theory of the sustainability of human migration and settlement in space - Irons, Lee G.; Irons, Morgan A. (Frontiers in Astronomy and Space Sciences, 2023)
It seems to be an accepted assumption that human migration into space is inevitable. Humans are a species of Earth. We are connected to Earth through evolution. We are also connected to space; our bodies contain heavy elements generated by fusion in the cores of stars. What does this evolutionary connection of humans to a star and a planet mean for their ability to inhabit space? This paper combines 100 years of research and scientific development of a theory of ecological thermodynamics with classical mechanics theory and analytical models of self-restoring heat engines to explain how the Sun and Earth have evolved into islands of order in the entropy of space. An explanation is provided regarding how naturally occurring conservative force fields engage a diversity of natural resources in semi-reversible cycles that build a high-exergy ecosphere. The science and evidence suggest that the ability to establish a human settlement in space without the self-restoring order, capacity, and organization of Earth will ultimately lead to settlement failure. Supply chains would disappear, market resources would be depleted, advancement in human pursuits would be disrupted, social and governance systems would falter or collapse, human population numbers would decline, genetic diversity in the human genome would be lost, average human individual biomass would decrease, and human knowledge and understanding would be forgotten. What does it mean to have a location in space outside of Earth be “like Earth?” The results of research are presented as a pancosmorio theory of human sustainability that is developed using the scientific philosophy methodology of abductive reasoning. Four analytical models of space ecosphere sustainability and five hypotheses with proposed tests for falsifiability are provided, including a theorem that suggests a limit to human expansion into space. A new quantitative method of human sustainability is developed from theories of network ecology, providing orthogonal properties of an ecosystem network stability function based upon an ecosystem network production function. Conclusions are made regarding the potential for sustainable development in space using balanced sustainability. Insights are provided regarding human endeavors on the Moon and Mars, as well as the Fermi paradox.